Effects of soluble guanylate cyclase activation on heart transplantation in a rat model - Loganathan, Sivakkanan; Korkmaz-İçöz, Sevil; Radovits, Tamás; Li, Shiliang; Mikles, Beatrice; Barnucz, Enikő; Hirschberg, Kristóf; Karck, Matthias; Szabó, Gábor (The journal of heart and lung transplantation, 2015)
Background - The nitric oxide (NO)/soluble guanylate cyclase (sGC)/cyclic guanosine monophosphate (cGMP) pathway is an important key mechanism to protect the heart from ischemia/reperfusion injury. However, this pathway is disrupted in several cardiovascular diseases as a result of decreased NO bioavailability and increased NO-insensitive forms of sGC. Cinaciguat preferentially activates these NO-insensitive, oxidized forms of sGC. - Methods - We assessed the hypothesis that targeting NO-unresponsive sGC would protect the graft against ischemia/reperfusion injury in a rat heart transplantation model. Before explantation, donor Lewis rats received methylcellulose (1%) vehicle or cinaciguat 10 mg/kg. The hearts were excised, stored in cold preservation solution, and heterotopically transplanted. We evaluated in vivo left ventricular function of the graft. - Results - After transplantation, decreased left ventricular systolic pressure (77 ± 3 mm Hg vs 123 ± 13 mm Hg, p < 0.05), dP/dtmax (1,703 ± 162 mm Hg vs 3,350 ± 444 mm Hg, p < 0.05), and dP/dtmin (995 ± 110 mm Hg vs 1,925 ± 332 mm Hg, p < 0.05) were significantly increased by cinaciguat. Coronary blood flow was significantly higher in the cinaciguat group compared with the control group. Additionally, cinaciguat increased adenosine triphosphate levels (1.9 ± 0.4 µmol/g vs 6.6 ± 0.8 µmol/g, p < 0.05) and improved energy charge potential. After transplantation, increased c-jun messenger RNA expression was downregulated, whereas superoxide dismutase-1 and cytochrome-c oxidase mRNA levels were upregulated by cinaciguat. Cinaciguat also significantly decreased myocardial DNA strand breaks induced by ischemia/reperfusion during transplantation and reduced death of cardiomyocytes in a cellular model of oxidative stress. - Conclusions - By interacting with NO-unresponsive sGC, cinaciguat enhances the protective effects of the NO/cGMP pathway at different steps of signal transduction after global myocardial ischemia/reperfusion. Its clinical use as pre-conditioning agent could be a novel approach in cardiac surgery.
Gesehen am 02.06.2020